Prediction of the Mental Toughness of the Athletes Based on Personality Traits - Zubic, Ivana M (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
The aim of this research is to examine connection between mental toughness of athletes and personality traits. The research sample consists of 100 athletes who participate in sports competitions. Mental Toughness was measured by "Sports Mental Toughness Questionnaire“ (SMTQ), HEXACO personality traits by HEXACO-60. The results showed statistically significant positive correlations between honesty, extraversion, conscientiousness on one side and self-confidence, consistency, control and overall mental toughness on other. Statistically significant negative correlations were found between emotionality on one hand and self-confidence, consistency, control, and overall mental strength on other. While correlations of agreeableness and openness to experience on one side and self-confidence, consistency, control and overall mental toughness on other were not statistically significant. Multiple regression analysis was performed with the aim of predicting the mental toughness of athletes based on personality traits. Of the total variability of mental toughness, 34% of variability can be explained based on personality traits of athletes. Statistically significant predictor of mental toughness is emotionality. Partial contributions of other personality traits were not statistically significant. This study contributed to the understanding of which personality traits of athletes contribute to mental toughness, coping mechanism with challenges and reacting in competitive situations.
Keywords: athletes; mental toughness; personality traits